Auto-donation entretiens et conférences - Henry, Michel 1922-2002 (Beauchesne, 2004)
Selection of interviews and conference presentations.
Keywords: Henry, Michel <1922-2002>; Fenomenologie; Philosophie; Phénoménologie; Vie; Phenomenology; Phänomenologie; Aufsatzsammlung